2017
DOI: 10.36685/phi.v3i3.125
|View full text |Cite
|
Sign up to set email alerts
|

Facility Assessment for Maternal and Child Health Services in Bangladesh Using Service Availability and Readiness Assessment (Sara) Tool: A Cross-Sectional Pilot Study

Abstract: Background: To initiate journey towards the Universal Health Coverage (UHC) it is essential to assess the health facilities. Unfortunately, no health facility assessment has been conducted in Bangladesh so far using “Service Availability and Readiness Assessment (SARA)” tool. Therefore, we aimed to conduct a pilot study to assess health facilities for maternal and child health services using SARA tool so that we can scale-up this assessment throughout the country later.Aim: We aimed to assess the health facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…This finding is similar to a study in Bangladesh, which reported low family planning services. 6 Intrauterine contraceptive devices (IUCDs) were provided by 40.7% of the PHC facilities in this study, which is higher than that reported by the study in Enugu, Nigeria, where only 18.3% of facilities provided IUCDs. 11 Only a few of the PHC facilities in this study offered HIV guidance and counselling testing for infants and PMTCT.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This finding is similar to a study in Bangladesh, which reported low family planning services. 6 Intrauterine contraceptive devices (IUCDs) were provided by 40.7% of the PHC facilities in this study, which is higher than that reported by the study in Enugu, Nigeria, where only 18.3% of facilities provided IUCDs. 11 Only a few of the PHC facilities in this study offered HIV guidance and counselling testing for infants and PMTCT.…”
Section: Discussioncontrasting
confidence: 65%
“…Universal Health Coverage (UHC) is required to achieve these goals, necessitating the assessment of health facility readiness to achieve UHC. 6 …”
Section: Introductionmentioning
confidence: 99%
“…17 Indeed, a research conducted among selected health facilities in Bangladesh also found that none of the facilities visited had EPI guidelines despite providing routine immunization. 18 The EPI guideline is an essential document meant to assist health workers in providing a standardized and uniformed immunization services. It is a valuable reference tool that should be readily available for consultation during routine immunization services or in-house supportive trainings.…”
Section: Discussionmentioning
confidence: 99%